Benefits of Menaming Dams and the Potential of Irrigation Canals as a Source of Power Generation - Yuli Handika Hasyim; Asral Asral (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2021)
The difficult location access and a small population can cause lack of electricity from PLN (State Electricity Company). One alternative that can be done is to use irrigation canals as a source of generation. In this study explained the social conditions of the community, the function of dams for the community and the potential of irrigation canals as a source of power generation. A case study was conducted in the Menaming Village in Riau Province. Menaming dam is one of the dams that have two main irrigation channels that can be used as a source of power generation. A quantitative descriptive method was used in this study. The results of the survey conducted by observing directly, questionnaires and data collection showed that Menaming dam was very beneficial for the Menaming’s community. Menaming dam is used as a source of water for rice fields and community ponds, access to community plantation land, fishing grounds and as a tourist attraction. Based preliminary study in Menaming dam was discovered the hydraulic water power in irrigation canals amounted to 1,330 watts. Therefore, it can be used as a source of power generation to meet the electricity needs of a simple house.